2023
DOI: 10.1002/pts.2729
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of multiple dispensing systems used for cosmetic product packaging

Abstract: Worldwide, the packaging industry for consumer product goods, including personal care and beauty products, generates over $25 billion in sales. An extremely high environmental impact follows the large demand in the industry. Almost 70% of the plastic waste generated in the cosmetics market is not recyclable. Sustainability in the beauty industry is complex and multifaceted, requiring an evaluation of all factors.Packaging plays an important role in the cosmetics market, and considering the amount of waste it g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…While the use of multiple datasets may increase its accuracy, LCA results studies have variously found the global warming potential of biodegradable mulch films to be 2-3 times lower than that for landfilling and incineration, and also, that composting and anaerobic biodegradation have a higher impact than incineration and energy recovery [228]. An airless pump that was found to have the lowest impact in all environmental categories relative to alternatives would have had the highest impact on ozone depletion if it were to be assumed that no lotion residue was left in the bottle [275].…”
Section: Assessing Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of multiple datasets may increase its accuracy, LCA results studies have variously found the global warming potential of biodegradable mulch films to be 2-3 times lower than that for landfilling and incineration, and also, that composting and anaerobic biodegradation have a higher impact than incineration and energy recovery [228]. An airless pump that was found to have the lowest impact in all environmental categories relative to alternatives would have had the highest impact on ozone depletion if it were to be assumed that no lotion residue was left in the bottle [275].…”
Section: Assessing Sustainabilitymentioning
confidence: 99%
“…Such issues are known in the literature; for instance, the aluminum pan of a reusable powder case was assumed to not be recyclable due to the possibility of powder residue [21]. Similarly, the presence or absence of residual lotion was shown to be significant for the determination of the relative environmental impacts of various potential products related to a bottle [275]. The issue is more whether consumers are aware of, or care for, such matters.…”
Section: Recyclementioning
confidence: 99%